Mengokohkan Otoritas Mufassir Melalui Uṣūl al-Tafsīr (Review Kitab ‘Ilm al-Tafsīr: Uṣūluhū wa Manāhijuhū karya Muhammad Afifuddin Dimyati) - Ahmad Syaifuddin Amin (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
The delaying of uṣūl al-tafsīr study in the world causes its stagnancy in Indonesia. Muhammad Afif Dimyathi as a productive scholar presented his work entitled “ilm al-tafsīr: Uṣūluhū wa Manāhijuhu as to answer the need of uṣūl al-tafsīr literature in Indonesia especially for Islamic universities. Containing 14 chapters, This book could systematically present some representative objects of uṣūl al-tafsīr study such as basic discussion of tafseer, methodology , trend and some rules of Qur’anic exegesis. By Afifuddin’s work, uṣūl al-tafsīr can be presented as simple and systematic object although in terms of content, He was still repeating objects discussed by other previous scholars. The affirmation of tafseer’s authority is a main character of  his tought arising from traditionalist culture.